2016
DOI: 10.4081/jlimnol.2016.1501
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of the vertical migration of Microcystis (cyanobacteria) colonies based on turbulence drag

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Movement of the Microcystis colony in turbulence can be considered analogous to the sediment transport process in turbulent currents 21 . The turbulent force, , on the Microcystis population under wind-driven current disturbance is composed of turbulent drag, virtual mass, and pressure-gradient forces.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Movement of the Microcystis colony in turbulence can be considered analogous to the sediment transport process in turbulent currents 21 . The turbulent force, , on the Microcystis population under wind-driven current disturbance is composed of turbulent drag, virtual mass, and pressure-gradient forces.…”
Section: Methodsmentioning
confidence: 99%
“…Wu et al 19 observed that Microcystis in Lake Taihu, with a colony size of 36–120 µm, were evenly distributed vertically under windy conditions and congregated at the surface when there was no wind. Laboratory test results from Xiao et al 20 and a numerical simulation test from Zhao et al 21 showed that the ability of Microcystis to resist the disturbance of wind-driven currents is positively correlated with colony size. Microcystis has a resistance limit for turbulent kinetic energy (TKE).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients in the waterbody also play a role in density change [5]. Additionally, turbulence and vertical water velocities can influence vertical migration in cyanobacteria [16].…”
Section: Discussionmentioning
confidence: 99%
“…Microcystis colonies in the Three Gorges Reservoir were observed to migrate to greater depths in open water while those in a protected enclosure stayed closer to the surface [12]. Zhao et al [16] found that Microcystis spp. (mainly M. aeruginosa) in a laboratory experiment could maintain buoyancy up to a critical value of turbulent kinetic energy, and that this value increased with colony size.…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…In turn, colony formation probably benefits 'nutrient, O 2 , and CO 2 exchange within the "phycosphere" by associated bacteria, thus minimizing nutrient (especially P) limitation (Paerl and Millie 1996;Cook et al 2019). Colony formation may also benefit the buildup of Microcystis biomass because of the high resistance of colonies to grazing pressure from zooplankton (Gerphagnon et al 2015), and an increased floating velocity of large colonies allowing more effective light capture in the upper water column even under wind-wave mixing (Zhao et al 2017), which is line with the positive correlation between colony size and biomass (Fig. 6a,b).…”
Section: Discussionmentioning
confidence: 99%